An ultra-compact four-port 4 × 4 superwideband MIMO antenna including mitigation of dual notched bands characteristics designed for wireless network applications - Sharma, Manish; Dhasarathan, Vigneswaran; Patel, Shobhit K.; Nguyen, Truong Khang (International journal of electronics and communications, 2020)
In this manuscript, four-port multiple-input-multiple-output (MIMO) superwideband antenna with mitigation of interfering bands is reported. The presented antenna comprises four identical patches which are placed orthogonal to each other. Rectangular ground plane to placed below the radiating patch forming monopole configuration and reduces the overall size of the antenna. Size reduction of antenna also has no change in wide operating bandwidth of the proposed antenna and interfering bands. Interfering bands which include WiMAX, LTE43 and WLAN are suppressed by using T-C shaped stubs/slots on the radiating patch and it is also worth noting that no separate isolation technique is used to achieve isolation between the radiating elements. Also, the inter-radiating patch maintains isolation of more than 20 dB with ECC (Envelope Correlation Coefficient) being less than 0.02 and TARC (Total Active Reflection Coefficient) less than 20 dB in operating bands. Single element, 2 × 2 MIMO, and 4 × 4 MIMO antenna is fabricated and confirms good agreement with simulated results.